Virtual Angklung Application using Adobe Flash - Oriega Ayudya; Raymond Bahana (Bina Nusantara University, 2019)
Virtual music instrument simulator is one of the most popular applications that people nowadays play, with this technology the user will be able to play music without necessarily having a real physical musical instrument. But recently, the virtual music instrument simulator that the developer develops are modern musical instruments such as guitar, drum, piano, etc., very few of them develop virtual simulators with traditional instruments such as Angklung. The aim of this thesis is to do research about how the people react to Angklung that will be developed virtually, and to develop virtual Angklung simulator using Adobe Flash for desktop that later can be embedded into web browser to accommodate the demand of the people who wants to play Angklung. The result of this application is successfully developed according to the proposed design, the scopes has been met. Based on the user acceptance test that has been conducted, 91% of the total respondents are satisfied with the prototype application and 88% of the total respondent said that they are still interested in using this application.